Karakterisasi Proses Gasifikasi Menjadi Listrik Berbahan Baku Sampah Padat Perkotaan Menggunakan Reaktor Tipe Downdraft di Provinsi Nusa Tenggara Barat - Shafwan Amrullah; Sopyan Ali Rohman; Cyrilla Oktaviananda; Fadhli Dzil Ikram (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
Indonesia is currently experiencing the problem of Municipal Solid Waste (MSW), energy and environmental crisis. Gasification by electric generator is the solution. This study about the design and characterization of the gasification reactor with MSW feed. This research was conducted by examining the effect of gasification temperature (550, 600, 650, 700, 750, 800, 850oC) and Air Fuel Ratio variations (0,5; 0,51; 0,53; 0,54l; and 0,55). The variabel test of temperature variations is syngas concentration, fuel conversion (FC), cold gas efficiency (CGE), carbon conversion efficiency (CCE), and specific fuel consumption (SCF). The AFR evaluated syngas and SCF. The result showed an increase the syngas levels with the increasing the gasification temperature, except CO2. The FC value increased(71% to 74%) and The CGE increases (77 to 97%). The CCE increases from 69% to 78% (550-650oC) and decreases again to 66% (850oC), and SCF decreased (4.5-0.5 kg/kWh). In the AFR variation, syngas levels increase with increasing AFR, but scf decreased (5.3 to 2), this proves efficient combustion.